Union sacrée 1914-193... - Rosmer, Alfred; Modiano, Hélène; Martinet, Marcel (Paris : J. Lefeuvre, 1936)
Fonds Perrone
Bibliotheek François Vercammen
Frans
Brochure
Keywords: Tweede Internationale (1889-1919).; Wereldoorlog 1